Codified Ordinances of the City of Cleveland, at 60, ch. 23, §§1-3 (1877). - (:unkn) unknown (My University, 1877)
§No person shall fire any cannon, gun, rifle, pistol or fire-arms of any kind, or fire or explode any squib, rocket, cracker, Roman candle, or other combustible fireworks within the city.
Keywords: DISCHARGE